ОБРАЗ ЯЗЫКА И ОБРАЗ БИОЛОГИЧЕСКОГО ВИДА С ПОЗИЦИЙ ОБЩЕЙ ТЕОРИИ РАЗВИВАЮЩИХСЯ СИСТЕМ И ТЕОРИИ УРОВНЕЙ НАУЧНОГО ЗНАНИЯ - Ейгер, Генріх Вільгельмович; Эпштейн, В.М. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article focuses on the issue of comparing language image with biological species image at theoretical level, і.е. in terms of General System Theory and Leveled Scientific Кnowledge Theory. Comparing biological species with language serves an underpinning for describing the notion of language image via such entities as form, features and functions of language. Its sixteen features and twelve functions are singled out.